Operational Analysis of Food Inventory in Warteg (Warung Tegal) Businesses Around Tangerang - Angelyn Meirvyrist; Cherrie Michelle Lie; Emily Charmaine; Fidelia Senaputra; Ivan Darrio; Sorensen Sukarta; Akeno Athallah Yahya; Nurhayati (Yayasan Pendidikan Tanggui Baimbaian, 2026)
This study examines inventory management and production capacity in warung tegal (warteg) businesses in Tangerang and surrounding areas, with a focus on the mismatch between production capacity and customer demand during peak hours. Warteg businesses typically prepare food in advance based on daily demand estimates, which often leads to operational risks such as food shortages or overproduction due to fluctuating demand, especially during lunchtime. Using a descriptive qualitative approach, data were collected through in-depth interviews and direct observations of 30 warteg businesses selected through convenience sampling. The analysis focuses on inventory-related indicators, including stock availability, frequency of stockouts, and replenishment practices during peak periods. The findings show that shortages frequently occur when popular menu items such as chicken and eggs run out before peak hours end. This is mainly caused by production decisions that rely on experience rather than structured inventory planning. This condition reduces service levels, resulting in longer waiting times and increased queues. The study suggests that implementing simple inventory management practices, such as recording daily sales patterns and determining buffer stock for high-demand menu items, can help optimize production planning, improve service efficiency, and reduce the risk of both shortages and food waste in small-scale food businesses.